Safety in Wireless Sensor Network: Types of Attacks and Solutions (International Journal of Engineering and Computer Science, 2016)
Wireless Sensor networks (WSNs) have become the most interesting regions of exploring in the 21st century. WSNs include a large number of sensor nodes, actuator nodes, gateways, and clients. Recent progress in wireless technologies has facilitated the vast variety of uses of WSNs in the military, traffic observation, target tracking, environment monitoring, healthcare monitoring, and so on. The designers of WSNs have been faced many new challenges, like sensed quantities, the size of nodes, and nodes’ autonomy. As a result, improved solutions to these confront and perfections in the modern technologies are required. The prospect expansions in sensor nodes must construct very influential and expenditure effective devices so that they may be used in applications. This paper also describes the modern research challenges for WSNs. And finally it reviews a number of security methods presently planned or implemented in WSNs. Key words: wireless sensor networks, Future trends, recent advances, research challenges etc.